ANALISIS EFEKTIFITAS MUSYAWARAH PERENCANAAN PEMBANGUNAN BIDANG INFRASTRUKTUR: (Studi Implementasi Hasil Musrenbang di Kecamatan Batupoaro Kota Baubau) - La Ode Alwi; Marsuki Iswandi; Bahari; Irfan Ido; Yursalam (Journal Publicuho, 2023)
The purpose of this research is to find out how the effectiveness of development meetings in Batupoaro District, Baubau City, regarding the implementation of infrastructure development results in 2020, and to formulate key indicators for the effectiveness of Musrenbang, Batupoaro District, Baubau City. The research was carried out in a qualitative and quantitative descriptive manner using data analysis methods, namely Interpretative Structural Modeling (ISM) and Important Performance Analysis (IPA). The sample used was 70 respondents who were determined by simple random sampling. The results showed that the implementation of the results of the Musrenbang on Batupoaro sub-district infrastructure was categorized as not yet/ineffective. While the key indicators driving the effectiveness of the Musrenbang Batupoaro District are: (1). Right on target, (2) Community needs, (3) Right program, (4) Budget availability, (5) Fairness, (6) Transparent, (7) Representative, (8) Accountability, (9) Responsiveness, (10) Participation, (11) Legal compliance, (12) Supervision, (13) HR implementation of Musrenbang, (14) Leadership commitment, (15) DPRD recess together with Musrenbang, (16 ) Policy formulation.